Rancang Bangun Mesin Pemipil Jagung Dengan Metode VDI 2222 - bunganaen, wenseslaus; Toai, Yopi; Mangesa, Daud P. (Universitas Nusa Cendana, 2022)
Corn farmers in general still use the traditional method of using their hands to separate the corn from the cobs, this requires more energy and time to separate the corn from the cobs. A shelling machine is needed as a means to assist farmers' needs in shelling corn to facilitate the existing shelling and save labor. The purpose of designing this corn sheller machine is to produce a design and produce a corn sheller machine for the needs of farmers in East Nusa Tenggara. The method of data collection and processing is carried out by applying the VDI (Verein Deutsche Inggenieur) 2222 method through 4 stages, namely analysis, design concept, design and embodiment. Based on the results of the planning of this corn sheller machine, the result of this corn sheller machine is that the shelled corn is clean from the corn cobs because it uses a soft material for shelling, namely rubber plucker so that it does not destroy the corn cobs.